Effect of Flow Distribution in Parallel Heat Exchanger Networks: Use of Thermo-Hydraulic Channeling Model in Refinery Operation - Masato Ishiyama, Edward; John Pugh, Simon (Heat transfer engineering, 2020)
Parallel branches are commonly observed in industrial heat exchanger networks (HENs). Despite the important relationship between flow distribution and network efficiency, not all parallel branches comprise of flow controllers or not least, flow measurements. When the network is subject to fouling, uncontrolled flow branches can introduce undesired phenomenon such as thermo-hydraulic channeling (THC) [presented at the 2007 HEFC conference; Ishiyama et al., Effect of fouling on heat transfer, pressure drop and throughput in refinery preheat trains]. Recent analysis of crude preheat train heat exchangers has shown the need to use THC models, in particular, for situations where there is insufficient flow measurement data, especially in nonsymmetric branches. This paper revisits the THC model and highlight practical importance of the THC phenomenon through analysis of plant data. The hydraulic aspect of the analysis is strongly linked to the knowledge of deposit thermal conductivity. A case study of a section of a crude refinery HEN is used to illustrate the use of thermo-hydraulic models in data reconciliation to understand flow imbalances caused due to differences in operating conditions and fouling of heat exchangers in each branch of a parallel network.